Biohistorical materials and contemporary privacy concerns-the forensic case of King Albert I. (September 2016) - Larmuseau, Maarten H.D.; Bekaert, Bram; Baumers, Maarten; Wenseleers, Tom; Deforce, Dieter; Borry, Pascal; Decorte, Ronny
Highlights: Genetic identification of relic with blood stains assigned to Belgian King Albert I. Identification confirms the official version on the death of King Albert I in 1934. Authentication of the relic was realised using a genetic genealogy approach. Publication of the genetic data would lead to privacy concerns for living relatives. Procedure is proposed towards balancing public research interests & privacy issues. Abstract: The rapid advancement of technology in genomic analysis increasingly allows researchers to study human biohistorical materials. Nevertheless, little attention has been paid to the privacy of the donor's living relatives and the negative impact they might experience from the (public) availability of genetic results, even in cases of scientific, forensic or historical relevance. This issue has become clear during a cold case investigation of a relic attributed to Belgian King and World War I-hero Albert I who died, according to the official version, in a solo climbing accident in 1934. Authentication of the relic with blood stains assigned to the King and collected on the place where his body was discovered is recognised as one of the final opportunities to test the plausibility of various conspiracy theories on the King's demise. While the historical value and current technological developments allow the genomic analysis of this relic, publication of genetic data would immediately lead to privacy concerns for living descendants and relatives of the King, including the Belgian and British royal families, even after more than 80 years. Therefore, the authentication study of the relic of King Albert I has been a difficult exercise towards balancing public research interests and privacy interests. The identification of the relic was realised by using a strict genetic genealogical approach including Y-chromosome and mitochondrial genome comparison with living relatives, thereby limiting the analysis to genomic regions relevant for identification. The genetic results combined with all available historical elements concerning the relic, provide strong evidence that King Albert I was indeed the donor of the blood stains, which is in line with the official climbing accident hypothesis and contradicts widespread 'mise-en-scène' scenarios. Since publication of the haploid data of the blood stains has the potential to violate the privacy of living relatives, we opted for external and independent reviewing of (the quality of) our data and statistical interpretation by external forensic experts in haploid markers to guarantee the objectivity and scientific accuracy of the identification data analysis as well as the privacy of living descendants and relatives. Although the cold case investigation provided relevant insights into the circumstances surrounding the death of King Albert I, it also revealed the insufficient ethical guidance for current genomic studies of biohistorical material.